2020
DOI: 10.1080/23750472.2020.1825988
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 lockdown on elite sportswomen

Abstract: Research question: The COVID-19 pandemic decimated elite level sport across the globe, although there were concerns that this impact affected women's sport much more so than for men's sport. This research considers the impact of the enforced global lockdown on elite women athletes, examining the immediate effect on their training practices, welfare and financial situation. Methods: A qualitative, online survey was used to collect anonymous data from 95 elite sportswomen. Data were coded to enable frequency ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
84
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(96 citation statements)
references
References 18 publications
8
84
1
3
Order By: Relevance
“…All other studies reported time spent in all subtypes of PA—for example, light, moderate, vigorous and walking—(if specified) decreased. Of the studies that measured PA changes as a percentage of the respective populations, eight studies 29 33 38 53 55 59 67 81 reported that >50% of the examined population decreased PA during lockdown, with all other studies reporting >50% of the examined population’s PA either stayed the same or decreased. For further information, see online supplemental table 5 .…”
Section: Resultsmentioning
confidence: 99%
“…All other studies reported time spent in all subtypes of PA—for example, light, moderate, vigorous and walking—(if specified) decreased. Of the studies that measured PA changes as a percentage of the respective populations, eight studies 29 33 38 53 55 59 67 81 reported that >50% of the examined population decreased PA during lockdown, with all other studies reporting >50% of the examined population’s PA either stayed the same or decreased. For further information, see online supplemental table 5 .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding gender, research addressing differences in how the pandemic hit male and female athletes has revealed a more negative impact of COVID-19 lockdown in female athletes ( di Fronso et al, 2020 ). In this line, Bowes et al (2020) identified some factors that might help to explain these differences in elite sport, such as a later resumption of the sport activity, greater difficulties for training at home, and a lesser financial support. As suggested in this study, future research in the field of youth sport should explore in more detail the sociological factors causing these gender differences beyond the impact of COVID-19 lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, interrupted training routines, financial problems (e.g., Andreato et al, 2020 ), social isolation, and distancing have increased ( Schinke et al, 2020 ). These developments may also include lack of communication among athletes and coaches (e.g., Jukic et al, 2020 ), reduced training quality and quantity in elite sportswomen ( Bowes et al, 2020 ) and handball players ( Mon-López et al, 2020 ) and the general population ( Maugeri et al, 2020 ). Furthermore, adverse behaviors such as drinking and smoking as well as eating and sleeping problems (e.g., Andreato et al, 2020 ; Maher et al, 2020 ), or increased gambling problems also in athletes ( Håkansson et al, 2020 ) are evident.…”
Section: Introductionmentioning
confidence: 99%